ECONOMIC FEASIBILITY OF LETTUCE INTERCROPPED WITH ROCKET IN FUNCTION OF SPACING AND GROWING SEASON - Nascimento, Carolina Seno [UNESP]; Nascimento, Camila Seno [UNESP]; Cecílio, Arthur Bernardes [UNESP] (Universidade Federal Rural do Semi-Árido, 2018)
Intercropping is a production system that can reduce the production cost and increase the profitability of vegetable producers, since it permits more efficient land and agricultural inputs use. In order to evaluate the effect of lettuce plant density on the economic feasibility of lettuce-rocket intercropping system over two growing seasons (winter and summer), two experiments were conducted in the field at São Paulo State University “Júlio de Mesquita Filho” (UNESP), Jaboticabal, São Paulo, Brazil. The treatments consisted of five lettuce-rocket intercrops with spacing between lettuce rows of: 0.20; 0.25; 0.30; 0.35 and 0.40 m, five sole crop of lettuce in the same spacing between rows adopted in the intercropping system, and a sole cropping of rocket with spacing between rows of 0.20 m. The statistical design adopted was the complete randomized block with four replicates. During winter, higher profitability was achieved with the highest population density. Highest profitability of the crops in both seasons was obtained in summer.

A consorciação de culturas é um sistema de produção capaz de reduzir os custos produtivos e aumentar a rentabilidade dos produtores de hortaliças, uma vez que ele possibilita o uso mais eficiente da área e dos insumos agrícolas. Com o objetivo de avaliar o efeito da densidade de plantas de alface na viabilidade econômica do consórcio de alface e rúcula, em duas épocas de cultivo (inverno e verão), dois experimentos foram instalados em campo, na Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP), Jaboticabal, São Paulo, Brasil. Os tratamentos corresponderam a cinco consórcios de alface com rúcula nos espaçamentos entre linhas da alface de: 0,20; 0,25; 0,30; 0,35 e 0,40 m, cinco cultivos solteiros de alface nos mesmos espaçamentos adotados em consórcio, e um cultivo solteiro de rúcula no espaçamento entre linhas de 0,20 m. O delineamento experimental utilizado foi em blocos casualizados completos, com quatro repetições. No inverno, maior rentabilidade é obtida com a maior densidade populacional. Maior rentabilidade das culturas, em ambas épocas de cultivo é obtida no verão.
VIABILIDADE ECONÔMICA DO CONSÓRCIO DE ALFACE E RÚCULA EM FUNÇÃO DO ESPAÇAMENTO E ÉPOCA DE CULTIVO
Keywords: Eruca sativa; Lactuta sativa; Profitability; Growth system.; Eruca sativa; Lactuca sativa; Rentabilidade; Sistema de cultivo